1999
DOI: 10.1111/0026-7902.00028
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Listening and Reading Rates of Japanese EFL Learners

Abstract: It has been claimed that the first language (L1) optimal listening rate (LR) is comparable to the reading rate (RR) of college students if the material is relatively easy (e.g., Hausfeld, 1981). However, it is questionable whether these two rates are comparable for second language (L2) learners who have not had the same amount of exposure to spoken English as L1 learners. This study seeks to find the answers to this question by establishing and examining the relationship between the LR and RR of 56 Japanese co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 43 publications
3
42
0
1
Order By: Relevance
“…It's important to consider the number of items in the interpretation of the internal consistency. For example, using the Spearman-Brown prophecy formula ( ; where n is the number of items and r is the actual reliability) in an application as done by Hirai (1999), we could find the factor 6 showing .90 instead .60 of internal consistency (considering more three items with the same intracorrelation as the actual three items). After defining the internal structure of the instrument, we conduced analyses to correlate the factors and total score with the factors and facets of the NEO-PI-R, PID-5 and MIS.…”
Section: Resultsmentioning
confidence: 99%
“…It's important to consider the number of items in the interpretation of the internal consistency. For example, using the Spearman-Brown prophecy formula ( ; where n is the number of items and r is the actual reliability) in an application as done by Hirai (1999), we could find the factor 6 showing .90 instead .60 of internal consistency (considering more three items with the same intracorrelation as the actual three items). After defining the internal structure of the instrument, we conduced analyses to correlate the factors and total score with the factors and facets of the NEO-PI-R, PID-5 and MIS.…”
Section: Resultsmentioning
confidence: 99%
“…That is, individuals will have the same comprehension no matter if they listen to or read a text, as long as the text is presented at their rauding rates (Carver, 1982(Carver, , 1992a(Carver, , 2000. Indeed, this contention was strongly supported by Hirai (1999), who found that the most efficient rate of reading comprehension for Japanese ESL learners correlated with their most efficient rate of listening comprehension at 0.94! Arons (1992) reports that the average rate of spoken English is between 130 and 200 words per minute.…”
Section: Pedagogical Implications Of Rauding Theory In L2 Language Edmentioning
confidence: 98%
“…It is assumed that language comprehension is an ability which is relatively constant, regardless of perception modality (Lund, 1991). Although it has been shown that reading and listening skills are highly correlated in both L1 (Sticht, 1972;Jackson & McClelland, 1979) and L2 (Hirai, 1999), research has revealed that there are some differences in comprehension performance between the two modalities among second language learners (Hirai, 1999;Lund, 1991).…”
Section: Introductionmentioning
confidence: 99%